2013
DOI: 10.1016/j.brainres.2012.11.034
|View full text |Cite
|
Sign up to set email alerts
|

ROCK2 regulates bFGF-induced proliferation of SH-SY5Y cells through GSK-3β and β-catenin pathway

Abstract: Increased neurogenesis by promoting proliferation of neural precursor cells in the adult dentate gyrus might be beneficial for the treatment of psychiatric disorders. Results demonstrate that bFGF is necessary for the proliferation of neural precursor cells and that the glycogen synthase kinase-3β (GSK-3β) and β-catenin pathway plays a role in it. However, the detailed mechanism of proliferation of neural precursor cells remains unclear. To elucidate that mechanism, we investigated the role of Rho-associated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…; Boku et al . ), it is possible that the pro‐adipogenic effect of bFGF on 2G11 cells would be mediated through activation of MAPK and GSK3β, and subsequent phosphorylation of C/EBPβ and C/EBPδ, resulting in an up‐regulation of both C/EBPα and PPARγ as observed in the present study.…”
Section: Discussionsupporting
confidence: 50%
“…; Boku et al . ), it is possible that the pro‐adipogenic effect of bFGF on 2G11 cells would be mediated through activation of MAPK and GSK3β, and subsequent phosphorylation of C/EBPβ and C/EBPδ, resulting in an up‐regulation of both C/EBPα and PPARγ as observed in the present study.…”
Section: Discussionsupporting
confidence: 50%
“…4 A). In addition, it has been reported that Rock2 can regulate its substrate protein by affecting the phosphorylation of Gsk‐3β [16]. Therefore, we speculated that Rock2 regulated CEBPD‐mediated HCC proliferation via the pGSK‐3β pathway.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, both ROCK1 and ROCK2 mediate insulin-stimulated insulin receptor substrate (IRS)-1 phosphorylation, but only ROCK2 binds directly to IRS-1. 62 Moreover, functional differences between ROCK1 and ROCK2 have been reported in fibroblasts, 6366 smooth muscle cells, 61,67 endothelial cells, 6872 keratinocytes, 7375 adipocytes, 62,65 neurons 66 and cancer cells. 76,77 These studies reveal that ROCK1 and ROCK2 have functional differences in regulating actin cytoskeleton, but the underlying mechanisms are not fully understood, which could be explained by the facts that both isoforms are expressed at different levels, distributed at different subcellular locations, and/or they have different interaction partners in individual cell types.…”
Section: Rock Isoform Functionsmentioning
confidence: 99%